Subsidized labour and firms: Investment, profitability, and leverage - Isaac Marcelin; Daniel Brink; David Oluwatosin Fadiran; Hammed Adedeji Amusa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Employing the difference-in-differences technique, this study examines the impact of the Employment Tax Incentive programme on a large sample of South African firms from 2011 to 2016. It finds that programme firms expanded investments by 4.8 per cent, and profits by 5.7 per cent. Consistent with the financial constraints theory, leverage rose by 6.63 per cent at smaller ETI firms, which are plagued with information asymmetry problems. Results imply both cost and liquidity mechanisms whereby the policy defrayed labour costs to boost profits and cash flows. Triple difference-in-difference estimates reveal that the policy had stronger effects at financially constrained firms. With important implications for labour markets and fiscal policies, the results suggest that well-designed youth wage subsidy policy schemes have the potential to enhance the prospects both of firms and of the economy more broadly.
Keywords: D22; F14; H32; J32; O47; 330; labour subsidy; investment; profitability; leverage